2012
DOI: 10.1093/gerona/gls219
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Does Not Increase Short-term or Long-term Protein Synthesis

Abstract: Increased protein synthesis is proposed as a mechanism of life-span extension during caloric restriction (CR). We hypothesized that CR does not increase protein synthesis in all tissues and protein fractions and that any increased protein synthesis with CR would be due to an increased anabolic effect of feeding. We used short- (4 hours) and long-term (6 weeks) methods to measure in vivo protein synthesis in lifelong ad libitum (AL) and CR mice. We did not detect an acute effect of feeding on protein synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 49 publications
(95 reference statements)
5
83
0
Order By: Relevance
“…Skeletal muscle tissue was fractionated according to our previously published procedures (4,5,13,14). Muscle (15-50 mg) was homogenized 1:10 with a bead homogenizer (Next Advance, Averill Park, NY) in isolation buffer (100 mM KCl, 40 mM Tris HCl, 10 mM Tris Base, 5 mM MgCl2, 1 mM EDTA, 1 mM ATP, pHϭ7.5) with phosphatase and protease inhibitors (HALT, Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Skeletal muscle tissue was fractionated according to our previously published procedures (4,5,13,14). Muscle (15-50 mg) was homogenized 1:10 with a bead homogenizer (Next Advance, Averill Park, NY) in isolation buffer (100 mM KCl, 40 mM Tris HCl, 10 mM Tris Base, 5 mM MgCl2, 1 mM EDTA, 1 mM ATP, pHϭ7.5) with phosphatase and protease inhibitors (HALT, Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Muscle (15-50 mg) was homogenized 1:10 with a bead homogenizer (Next Advance, Averill Park, NY) in isolation buffer (100 mM KCl, 40 mM Tris HCl, 10 mM Tris Base, 5 mM MgCl2, 1 mM EDTA, 1 mM ATP, pHϭ7.5) with phosphatase and protease inhibitors (HALT, Thermo Scientific, Rockford, IL). After homogenization, subcellular fractions of mixed (Mixed, containing primarily contractile elements and nuclei), cytosolic (Cyto), and mitochondrial (Mito) proteins were isolated via differential centrifugation as previously described (4,5,13,14). After muscle fractions were isolated and purified, 250 l 1 M NaOH was added, and pellets were incubated for 15 min at 50°C and 900 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Declining food intake does not correlate with low serum protein levels and vice versa [37]. Miller et al [38] has demonstrated no effect of acute feeding (4 h) on protein synthesis. Decrease in plasma volume on a CR regime causes hypohydration, which thereby leads to an overall decrease in the blood volume.…”
Section: Discussionmentioning
confidence: 95%